Changes of Physicochemical Characteristics of Microplastics During Water Disinfection Processes: A Review - Shuo ZHANG; Xian ZHANG; Hang LIU; Chenhao TIAN; Miao WANG; Guoqi SHI; Chao LIU (能源环境保护)
Microplastic pollution in aquatic environments has drawn widespread attention. In addition to the toxicity and ecological risks, microplastics can act as carriers of various pollutants. In water disinfection processes, disinfectants can induce changes in the physicochemical characteristics of microplastics and cause the release of toxic additives. The characteristic changes can affect the adsorption of organic pollutants by microplastics, thereby altering the fate and transformation of these pollutants. This review summarizes variations in the functional groups, hydrophobicity, morphology, and particle size of microplastics during representative water disinfection processes (e.g., chlorination, ozonation, and UV). The adsorption of organic pollutants onto microplastics, after disinfection, is discussed. Chlorine is reactive towards microplastics with aromatic ring, amide, and ester groups. The oxygen transfer and electrophilic substitution pathways lead to the formation of oxygen rich groups (e.g., C=O and C—O) and chlorine-containing groups (e.g., C—Cl). The formation of oxygen-enriched groups with high polarity decreases the hydrophobicity of microplastics, whereas the formation of chlorine-containing groups increases the surface hydrophobic. In the ozonation process, microplastics could be oxidized directly by molecular ozone or the secondarily formed OH radical. Due to the strong oxidation capacity of ozone, abundant oxygen-enriched groups, such as C=O, can be observed in ozonated microplastics, resulting in decreased hydrophobicity. The reaction between microplastics and OH radicals leads to the formation of hydroxylated groups. UV damages the functional groups of microplastics via direct photolysis or radical formation. UV can induce chain scission on chromophore-containing microplastics (e.g., polystyrene), while microplastics without chromophore (e.g., polyethylene) can be degraded by radical-induced oxidation. In the presence of low doses of ozone and UV irradiation, the surface roughness of microplastics decreases. However, pores and cracks could be formed with increasing doses of disinfectants, increasing surface roughness and decreasing particle size of microplastics. Adsorption mechanisms of organic pollutants onto microplastics include hydrophobic interactions, hydrogen bonding, electrostatic interactions, and π—π stacking. Reduced hydrophobicity weakens organic pollutant adsorption by microplastics, whereas increased surface roughness enhances interaction sites between microplastics and organic pollutants. In addition, the damage to aromatic rings of microplastics reduces π—π stacking forces, weakening their adsorption capacity for aromatic organic compounds. Due to the predominant role of hydrophobicity in hydrophobic organic adsorption, disinfection may lead to their release. Finally, this review also identifies several knowledge gaps to highlight future research topics of interest.